1995
DOI: 10.1128/jb.177.21.6195-6200.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a benzylviologen-linked, tungsten-containing aldehyde oxidoreductase from Desulfovibrio gigas

Abstract: Desulfovibrio gigas NCIMB 9332 is a sulfate-reducing bacterium which is able to grow with H 2 , L-and D-lactate, C 4 -dicarboxylic acids, and ethanol as energy sources (17,35). D. gigas not only oxidizes ethanol (to acetate) but it can also store massive amounts of polyglucose (29) which under fermentative conditions can be degraded with ethanol as a major end product (26).Recently, we characterized the NAD-dependent alcohol dehydrogenase from D. gigas and showed it to be an oxygen-labile, decameric enzyme (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 39 publications
5
61
0
Order By: Relevance
“…Different authors seem to agree that Wcontaining isoenzymes represent, apparently, less evolved forms or ancestors of the Mo-containing enzymes [3,5,51]. In this context, the existing Wcontaining enzymes, such as D. gigas and S. fumaroxidans Fdhs [3,4], would represent a group of enzymes that cannot adopt Mo to accomplish a specific function in living organisms, which along evolution were substituting Mo for W in enzymes.…”
Section: Incorporation Of Either Mo or W In Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…Different authors seem to agree that Wcontaining isoenzymes represent, apparently, less evolved forms or ancestors of the Mo-containing enzymes [3,5,51]. In this context, the existing Wcontaining enzymes, such as D. gigas and S. fumaroxidans Fdhs [3,4], would represent a group of enzymes that cannot adopt Mo to accomplish a specific function in living organisms, which along evolution were substituting Mo for W in enzymes.…”
Section: Incorporation Of Either Mo or W In Enzymesmentioning
confidence: 99%
“…The inverse reaction, the conversion of CO 2 to formate, has been demonstrated in a few cases, and this activity was found to be exclusive for W-Fdh proteins [4]. Consequently, it was suggested that the reduction of CO 2 to formate is W-dependent, whereas the inverse reaction in anaerobes is performed exclusively by Mo-containing enzymes [4]. Additional studies should be performed to verify whether the mechanism proposed for E. coli Fdh-H is valid for all formate dehydrogenases [13] and if the conversion of CO 2 to formate is exclusive for W-Fdh proteins [5].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…nase [3,4], carboxylic acid reductase [5,6] and aldehyde dehydrogenase [7,8]. Most mesophilic, MoϪdependent organisms, when grown in the presence of tungstate, produce either inactive enzymes lacking any metal or W-substituted enzymes that have little or no catalytic activity [2].…”
mentioning
confidence: 99%